Analisis Pengaruh Perubahan Arus Kas terhadap Return Saham (Management Analysis Journal, 2015)
The purpose of this study was to determine the influence of the operating cash flow, the financing cash flow, and the influence of the investing cash flow to the stock returns, as well as to determine the influence of the operating cash flow, the financing cash flow, and the investing cash flow together equally against the stock returns. Number of sample that used in this research is 30 samples with the method purposive sampling. Based on the results of simultaneous research indicate that the operating cash flows, the financing cash flows and the investing cash flows did not have any influence on the stock returns. The result of research partially known that the operating cash flow has not an effect on stock returns, the financing cash flow has not an effect on stock returns, and the investment cash flow has not an effect on stock returns. The research concluded that the operating cash flow, the financing cash flow, and the investing cash flow did not have any influence on the stock returns, either simultaneously or partially. The suggestions of the research is for the investors and the potential investors or other stockholders taking into account the information of a company’s cash flow from the operating cash flows, the financing cash flows and the investing cash flows to predicting the stock returns.